Del rascacielos al rascasuelos : La casbah japonesa de Rem Koolhaas - Álvarez Arce, Raquel (2016)
Rem Koolhaas, as a contemporary architect, draws from the proposals which were devel-oped by the architects who reacted to the ideas formulated on the International Congresses of Modern Architecture, like the Team 10 members. Woods, along with Candilis and Josic, worked out a new type of building that he called ground-scrapper, although it is better known by the name given by Alison Smithson: the mat-building. Rem Koolhaas, in the Nexus World building in Fukuoka, propose, as he says in S,M,L, XL, a house building which is a combina-tion of Mies’s court houses and the ones in the ancient Rome, forming continuous tapestries where houses never become objects. Definitely, he proposes a mat-building. OMA’s head-master applies what he had learn with “Delirious New York” and he introduces the skyscraper features in his own ground-scrapper, redefi ning the mat-building.